Rapid α-Amination of N-Substituted Indoles by Using DBU-Activated N-Haloimides as Nitrogen Sources - Li, Yanru; Zhang, Luyan; Yuan, Haiyan; Liang, Fushun; Zhang, Jingping (Synlett, 2015)
By using the N-haloimide/DBU protocol, the electrophilic imidation at C2-position of N-substituted indoles has been achieved in high efficiency. The dual activation of N-haloimide by DBU to simultaneously achieve a more electrophilic bromine and a more nucleophilic nitrogen atom, is demonstrated to be crucial in this transformation. The process involves tandem bromonium ion formation, electrophilic addition, and elimination of HBr. The protocol provides a novel, efficient, green, and complimentary access to α-imidated indoles under mild conditions, without the necessity of external nitrogen sources.
Keywords: indoles; amination; N-haloimides; DBU